Disrupted Social Hierarchy in Prenatally Valproate-Exposed Autistic-Like Rats - Pelsőczi, Péter; Kelemen, Kristóf; Csölle, Cecília; Nagy, Gábor; Lendvai, Balázs; Román, Viktor; Lévay, György (Frontiers in Behavioral Neuroscience, 2020)
Autism spectrum disorder (ASD) is characterized by impaired socio-communicational function, repetitive and restricted behaviors. Valproic acid (VPA) was reported to increase the prevalence of ASD in humans as a consequence of its use during pregnancy. VPA treatment also induces autistic-like behaviors in the offspring of rats after prenatal exposure; hence it is a preclinical disease model with high translational value. In the present study our aim was to characterize ASD relevant behaviors of socially housed, individually identified male rats in automated home cages. Natural behavior of rats was assessed by monitoring their visits to drinking bottles in an environment without human influence aming at reducing interventional stress. Although rodents normally tend to explore their new environment, prenatally VPA-treated rats showed a drastic impairment in initial and long-term exploratory behavior throughout their stay in the automated cage. Furthermore, VPA rats displayed psychogenic polydipsia as well as altered circadian activity. In the competitive situation of strict water deprivation controls switched to an uneven resource sharing and only a few dominant animals had access to water. In VPA animals similar hierarchy-related changes were completely absent. While the control rats secured their chance to drink with frequent reentering visits, thereby ‘guarding’ the water resource, VPA animals did not switch to uneven sharing and displayed no evidence of guarding behavior.